Experimentation Of Video Based Learning Methods With Game Based Learning In Improving Students' Understanding Of Mathematical Concepts - Sinta Mawalia; Heru Agni Setiaji (Universitas Wiralodra, 2025)
The low level of students' understanding of mathematical concepts is a crucial problem in education that has an impact on academic achievement in general, so innovation in learning methods is needed. This study aims to compare the effectiveness of video-based learning (VBL) and game-based learning (GBL) in improving students' understanding of mathematical concepts. This study adopted a quasi-experimental design with two experimental classes, each using the VBL and GBL methods, and a control class with traditional learning methods. The research instruments were pre-test and post-test essay tests that were validated and reliable. The results of data analysis using One Way ANOVA proved that there were significant differences between the 3 groups. The VBL and GBL approaches proved to be more effective than the traditional approach in improving students' mathematical understanding of mathematical concepts. This study suggests the use of video and game-based learning methods as innovative alternatives to improve the quality of mathematics learning in schools.